Nurse's Obstacles In Delivering End Of Life Care - Reni Sulung Utami; Ayu Karunia Putri ((JKG) Jurnal Keperawatan Global, 2022)
Background: Death can occur in any situation at any time, and each hospital setting has different difficulties in providing high-quality end-of-life care. The hospital's Islamic culture might offer new experiences to nurses when providing EOLC and be related to the challenges they face. This study identified the difficulties nurses encounter when providing end-of-life care in an Islamic-based hospital. Methods: A descriptive cross-sectional survey was applied to this study. A questionnaire that was adapted from the Nursing Survey Questionnaire Regarding End-of-Life Care on Medical-Surgical Units was used to collect the data. The translation and back-translation processes were carried out in the Indonesian version. All questionnaire items were declared valid with a validity value range of 0.820 to 0.950 (r table = 0.312), and the reliability test results obtained an alpha coefficient value of 0.977 (very reliable). The consecutive sampling method was applied. The data were analyzed using univariate analysis. At an Islamic hospital in Semarang, 97 surgical and medical nurses in total participated in the survey. Results: The findings indicate that the three main obstacles to nurses delivering end-of-life care are knowledge gaps (x = 2.53), a lack of education or training (x = 2.34), and health professionals’ avoidance of dying patients (x = 2.30). Other major impediments include a lack of family acceptance and uncooperative family attitudes. Conclusion: Nurses and family factors are the biggest obstacles for nurses in caring for dying patients.